2016
DOI: 10.1016/j.jmb.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Cysteine within the ATPase Domain of the Endoplasmic Reticulum Chaperone BiP is Necessary for a Complete Complement of BiP Activities

Abstract: Among the amino acids, cysteine stands apart based on its highly reactive sulfur group. In general, cysteine is underrepresented in proteins. Yet when present, the features of cysteine often afford unique function. We have shown previously that a cysteine within the ATPase domain of yeast BiP (Kar2) serves as a sensor of the endoplasmic reticulum (ER) redox environment [1, 2]. Under conditions of increased oxidant (oxidative stress) this cysteine becomes oxidized, changing Kar2 from an ATP-dependent foldase to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
(84 reference statements)
2
15
0
Order By: Relevance
“…49 Notably, studies of different amino acid substitutions of the conserved BiP cysteine in yeast revealed also the strongest phenotypes with a BiP C 63 W allele, relative to a BiP C 63 K mutant. 50…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Notably, studies of different amino acid substitutions of the conserved BiP cysteine in yeast revealed also the strongest phenotypes with a BiP C 63 W allele, relative to a BiP C 63 K mutant. 50…”
Section: Discussionmentioning
confidence: 99%
“…49,55 As mentioned above, these observations are consistent with our prior data relating to BiP, which demonstrated a more severe effect on chaperone activities for a BiP C 63 W mutation than for a C 63 K mutation. 50…”
Section: Discussionmentioning
confidence: 99%
“…63p [139]. The ATPase domain of BiP contains a conserved cysteine (Cys63) [140], which can be sulfenylated [138] or glutathionylated [60], suggesting a redox-regulated mechanism of BiP release and UPR initiation. The redox regulation of BiP function is delicate.…”
Section: Redox Modifications Of Upr Sensors Controlling Cell Fatementioning
confidence: 99%
“…Residues C52 and C57 of Sil1 have recently been shown to form a redox-active cysteine pair that facilitates the reduction of C63 in the ATPase domain of Kar2 (8). Oxidation of C63 impairs Kar2's ATPase activity, altering its chaperone function to cope with the suboptimal folding conditions that arise during oxidative stress (8)(9)(10)(11). Sil1 can then reduce the oxidized cysteine residue in the BiP ATPase domain to restore ATPase activity and chaperone function once the levels of oxidative stress in the ER have subsided.…”
Section: Discussion N-glycosylation Enables Sil1mentioning
confidence: 99%
“…Upon increased ER oxidation, a highly conserved cysteine residue, C63, within the ATPase domain of BiP becomes oxidized (8,9). This alters BiP/Kar2 chaperone activity to limit polypeptide aggregation during suboptimal redox conditions for ER protein folding (9)(10)(11). Reductive stress also gives rise to the accumulation of misfolded proteins.…”
mentioning
confidence: 99%